Advancements in Disaster Management: Insights into Risk Assessment, Mitigation, and Funding Strategies - Alfi Rahman (International Journal of Disaster Management, 2023)
This edition showcases a diverse range of research articles that offer valuable insights into various aspects of disaster management. The articles included in this issue address crucial topics in the field. For instance, Lendra et al. present a study on occupational safety and health risk management in the construction industry during the COVID-19 pandemic, proposing control solutions to ensure worker safety. Arrisaldi et al. focus on landslide risk assessment using Geographic Information System (GIS) in Kulon Progo, Indonesia, providing a comprehensive landslide risk map for disaster preparedness and community resilience. Indira and Manessa explore the generation of effective tsunami evacuation routes based on hazard models in Sukabumi, West Java, emphasizing the importance of revising hazard maps and identifying optimal routes to enhance the safety and preparedness of coastal communities. Irsyadillah investigates the concept of disaster capitalism and its impact on safety culture within the aviation industry. Other topics covered in this issue include spatio-temporal analysis of ground movement using unmanned aerial vehicles (UAV) photogrammetry by Amalia et al., analysis of hydraulic jumps for dam safety, examination of changes in mobility patterns and CO2 emissions during the pandemic by Fatimah et al. and Darma et al., understanding socio-ecological differences and risks faced by indigenous communities by Sunarti et al., exploring funding strategies through the Land Value Capture (LVC) scheme by Handayani et al., and conducting a bibliometric study on disaster management agencies and public policy by Kurniawati et al. These research articles significantly contribute to advancing knowledge in disaster management and provide practical insights for researchers, policymakers, and practitioners. We encourage readers to delve into these articles and participate in further discussions on the vital field of disaster management.